DISTRIBUTION AND POTENTIAL OF CAMELLIA SPP. IN THE CENTRAL HIGHLANDS, VIETNAM, FOR DEVELOPING HIGH-VALUE PRODUCTS IN THE FOOD INDUSTRY - Nguyen, Thi Thang Long (Trường Đại học Đà Lạt, 2024)
This article focuses on the potential use of yellow camellias in the food technology industry by analyzing and synthesizing information from previous publications. Many rare species of the genus Camellia have been discovered recently in the Central Highlands of Vietnam, including 10 new species discovered in Lam Dong Province between 2012 and 2016. These 10 species account for 55.55% of the 18 species growing naturally in the Central Highlands and demonstrate the diversity of Camellia in the region. The flowers range from light yellow to orange to deep yellow in color. The survival rate of cuttings is 72.24%–83.33%, and the rooting rate when seeds are sown approaches 100%. Yellow camellias do not contain caffeine. The main active ingredient is polyphenol, with a content of 5.22%–30.11% (mg GAE/100 g DW). Camellia extract does not cause acute toxicity and has a blood sugar-lowering effect. Vietnam has much experience growing green tea; the total green tea growing area is 131,200 hectares. The average annual yield is 6.90 tons of fresh leaves per hectare, and the current export market to 60 countries is the basis for expanding the yellow camellias growing area. The Central Highlands has great potential as a stable source of raw materials to create fermented beverages, tea powder, tea oil, and colorants.